2022
DOI: 10.1007/s12144-022-03631-9
|View full text |Cite
|
Sign up to set email alerts
|

Minority stressors, protective factors and mental health outcomes in lesbian, gay and bisexual people in the UK

Abstract: Two cross-sectional survey studies were conducted to examine the relationships between minority stressors, protective factors and mental health outcomes in lesbian, gay and bisexual people (LGB) in the United Kingdom (UK). A convenience sample of 156 LGB people in the UK participated in Study 1. Multiple regression analyses showed that victimization and sexuality-related identity threat were positively associated with anxiety and that identity resilience, social support and degree of outness were negative corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…In relation to formal healthcare settings, participants of the wider research project that this paper draws from have highlighted the negative impacts of limitations of child and adolescent mental health services (CAMHS), particularly increasing waiting times, on the young people who try to engage with them (Holding et al, 2022). Our participants argued that CAMHS are not serving LGBTQ þ young people appropriately, despite their increased risk of mental health problems (Carlile, 2020;Jaspal et al, 2022;Westwood et al, 2020). Further, adults in positions of authority acting in discriminatory ways compounded mental and emotional distress.…”
Section: Health Inequalities As Socially Determined Intersectional Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to formal healthcare settings, participants of the wider research project that this paper draws from have highlighted the negative impacts of limitations of child and adolescent mental health services (CAMHS), particularly increasing waiting times, on the young people who try to engage with them (Holding et al, 2022). Our participants argued that CAMHS are not serving LGBTQ þ young people appropriately, despite their increased risk of mental health problems (Carlile, 2020;Jaspal et al, 2022;Westwood et al, 2020). Further, adults in positions of authority acting in discriminatory ways compounded mental and emotional distress.…”
Section: Health Inequalities As Socially Determined Intersectional Co...mentioning
confidence: 99%
“…Lesbian, gay, bisexual, transgender, queer/questioning, intersex, asexual/agenderþ (LGBTQ þ hereafter) people report poorer health and worse experiences of healthcare than the general population (McDermott, Gabb, et al, 2021;Carlile, 2020;Westwood et al, 2020;Gnan et al, 2019;Jaspal et al, 2022). In line with a social determinants of health (SDH) perspective, this paper looks beyond the healthcare setting to view health as situated within wider complex health systems, by reflecting on injustices that result from power imbalances and unequal access to resources and reduced opportunities to lead healthier lives (Marmot et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Proximal stressors reflect the individual's internal response to these events, such as internalized homonegativity, that is, the acceptance of negative social representations of their sexual orientation. It has been found that these distinct types of stressors may contribute differently to depressive and anxious symptomatology in sexual minorities [52,53]. In order to understand how and why particular types of stressors affect mental health, it is important to understand the individual's sense of identity.…”
Section: Exposure To Stressorsmentioning
confidence: 99%
“…This has conversely been a key focus of identity process theory. Jaspal and colleagues [44,52] have shown that minority stressors that cause identity threat, that is, those that succeed in curtailing feelings of self-esteem, self-efficacy, positive distinctiveness and self-efficacy, tend to be associated with greater levels of distress, anxiety and depression. It seems important, therefore, to measure not only reported exposure to stressors and which ones but also the ways in which they impact on identity processes in gay and bisexual men.…”
Section: Exposure To Stressorsmentioning
confidence: 99%
See 1 more Smart Citation